PENGENDALIAN PELAKSANAAN PROYEK DITINJAU DARI SEGI WAKTU PADA GEDUNG RRC DI PROYEK REKONTRUKSI DAN PENINGKATAN UNP - Nasrul Nasrul; Rosi Maida Astuti (Rang Teknik Journal, 2020)
To monitor and control the timing of the project needs to use one method that meets these goals is a network (network planning) concept of the value of the results ( earned value concept) in the form of a schedule of integrated (schedule variance ), which consists of three indicators , namely BCWS , BCWP , and ACWP , Research procedure begins with a feasibility study case , collecting data , and analyzing the results from the available data.